Produktivitas Pengarang Menggunakan Hukum Lotka Dengan Teknik Complete Count Pada Jurnal Kedokteran YARSI Tahun 2009-2018 - Kangko, Danang Dwijo; Rahmadhani, Rahmadhani; Erza, Elfitri Kurnia (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2020)
Researchers research to develop science. Research results are published as a form of scientific communication. One type of scientific publication is a journal article. YARSI Medical Journal is a peer-reviewed journal in the field of medicine and health that is open to the public owned by YARSI University. The author's productivity patterns in the YARSI Medical Journal so far are unknown. Author productivity is the number of papers produced by the author on a particular subject and published in scientific journals in a certain period. This study aims to (1) Determine the author's productivity patterns using Lotka's Law with complete count techniques in YARSI Medical Journal 2009-2018; (2) Testing the suitability of the frequency of Lotka's Law with the author's frequency distribution using the complete count technique in YARSI Medical Journal 2009-2018. The research method used in this study is a quantitative method with bibliometric analysis. Data collection uses documentation method. The results of this study include (1) the pattern of author productivity with an exponent value (n) 2.874110535 and the constant (C) 0.820080499 meaning that the author contributing to one article is 82.00% of the total number of authors, it can be said that the YARSI Medical Journal Author Productivity Pattern 2009- 2018 is low or less productive. (2) Based on the K-S test the maximum deviation is 0 and the critical value is 0.0829206. Dmax is smaller than the critical value, so H0 is accepted. That is, the Author Productivity Pattern uses the Complete Count Technique in YARSI Medical Journal 2009-2018 following Lotka's Law.